The role of radiation therapy and margin width in localized soft‐tissue sarcoma: Analysis from the US Sarcoma Collaborative. Issue 3 (6th June 2019) - Gannon, Nicholas P.; King, David M.; Ethun, Cecilia G.; Charlson, John; Tran, Thuy B.; Poultsides, George; Grignol, Valerie; Howard, J. Harrison; Tseng, Jennifer; Roggin, Kevin K.; Votanopoulos, Konstantinos; Krasnick, Bradley; et al.
Abstract: Background and Objectives: Soft‐tissue sarcomas (STSs) are often treated with resection and radiation (RT)±chemotherapy. The role of RT in decreasing resection width to achieve local control is unclear. We evaluated RT on margin width to achieve local control and local recurrence (LR). Methods: From 2000 to 2016, 514 patients with localized STS were identified from the US Sarcoma Collaborative database. Patients were stratified by a margin and local control was compared amongst treatment groups. Results: LR was 9% with positive, 4.2% with ≤1 mm, and 9.3% with >1 mm margins ( P  = .315). In the ≤1 mm group, LR was 5.7% without RT, 0% with preoperative RT, and 0% with postoperative RT ( P  < .0001). In the >1 mm group, LR was 10.2%, 0%, and 3.7% in the no preoperative and postoperative RT groups, respectively ( P  = .005). RT did not influence LR in patients with positive margins. In stage I‐III and II‐III patients, local recurrence‐free survival was higher following RT ( P  = .008 and P  = .05, respectively). Conclusions: RT may play a larger role in minimizing LR than margin status. In patients with positive margins, RT may decrease LR to similar rates as a negative margin without RT and may be considered to decrease the risk of LR with anticipated close/positive margins.